Genetic Diversity - Recent Advances and Applications 2023
DOI: 10.5772/intechopen.105984
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Variability of Three Types of Sorghum Cultivated in Burkina Faso Using Morphoagronomic Quantitative Traits and Brix

Abstract: In Burkina Faso, tree types of sorghum are mainly grown. Despite their genetic proximity revealed by molecular markers, the identification of distinctive agro-morphological traits between sweet grain sorghum, sweet sorghum and grain sorghum could contribute to better management of their genetic resources. Thus, 42 genotypes consisting of the three sorghum types were evaluated in a three replicate Fisher incomplete block design using 20 quantitative traits. The results showed a high variability of traits within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In Burkina Faso, since 2008, many investigations have been undertaken by University of Ouagadougou (current University Joseph Ki-Zerbo) for the sweet stalk sorghum potential. These efforts focused on the characterization of its genetic diversity and the Brix content in the stalk [13][14][15], the evaluation of the photoperiod sensitivity of genotypes [13], and the genetic relationships between this sorghum and other types of sorghum grown [14][15][16]. All of these studies have shown significant genetic diversity within sweet stalk sorghum, high sensitivity to photoperiod, and close genetic proximity among grain sorghum and sweet grain sorghum.…”
Section: Introductionmentioning
confidence: 99%
“…In Burkina Faso, since 2008, many investigations have been undertaken by University of Ouagadougou (current University Joseph Ki-Zerbo) for the sweet stalk sorghum potential. These efforts focused on the characterization of its genetic diversity and the Brix content in the stalk [13][14][15], the evaluation of the photoperiod sensitivity of genotypes [13], and the genetic relationships between this sorghum and other types of sorghum grown [14][15][16]. All of these studies have shown significant genetic diversity within sweet stalk sorghum, high sensitivity to photoperiod, and close genetic proximity among grain sorghum and sweet grain sorghum.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has highlighted farmers' management methods and genetic diversity within each type of sorghum, including grain sorghum [2] [3] [14], sweet grain sorghum [15] [16] [17] and sweet stem sorghum [6]. Other studies of genetic diversity and comparison of sorghum types at the agromorphological [18] [19] and molecular [20] [21] levels have shown the proximity to its sorghums. However, the impact of the coevolution of the different sorghum types on the organization of the diversity of these sorghums is still unknown in Burkina Faso, which could constitute a limiting factor in the management of its sorghums.…”
Section: Introductionmentioning
confidence: 99%